2004
DOI: 10.1081/cbi-200025981
|View full text |Cite
|
Sign up to set email alerts
|

Altered Circadian Relationship Between Serum Nitric Oxide, Carbon Dioxide, and Uric Acid in Multiple Sclerosis

Abstract: The free radical nitric oxide (NO*) is involved in a variety of diverse biological processes from acting as a vasodilator in the cardiovascular system to being the rate-limiting component in the production of peroxynitrite (ONOO-), a contributor to neurodegenerative disorders such as multiple sclerosis (MS). Uric acid (UA), the end product of purine metabolism in humans and a selective inhibitor of toxic reactions attributed to radicals formed by the interaction of ONOO- and CO2, is generally low in MS patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…UA is a powerful antioxidant (Hooper et al 2000) and has a protective role of vitamins E and C (Ma et al 1994). However, to date, only few studies have investigated the diurnal variations of TAS (Benot et al 1999;Borisenkov et al 2007) and UA (Kanabrocki et al 1990(Kanabrocki et al , 2004 in human. These investigations found that acrophases of TAS and UA were observed in the early morning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…UA is a powerful antioxidant (Hooper et al 2000) and has a protective role of vitamins E and C (Ma et al 1994). However, to date, only few studies have investigated the diurnal variations of TAS (Benot et al 1999;Borisenkov et al 2007) and UA (Kanabrocki et al 1990(Kanabrocki et al , 2004 in human. These investigations found that acrophases of TAS and UA were observed in the early morning.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Kanabrocki et al (1990Kanabrocki et al ( , 2004 concluded that the peak values of uric acid (UA) are situated around 02:00 h. Although origins of these fluctuations are unclear, it has been identified that the physiological levels of melatonin contribute to total antioxidant capacity of human serum (Benot et al 1999), this hormone having a powerful antioxidant role (Tan et al 1993). However, these studies used healthy individuals with average age generally 30 years (Kanabrocki et al 1990(Kanabrocki et al , 2004Rivera-Coll et al 1993).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Despite data are still scarce, studies point to an increased cardiovascular risk (CVR) in patients with MS, at least when compared with individuals of similar age [3][4][5]. MS patients exhibit autonomic dysfunc-tion [6], increased blood pressure and tachycardia [7], ventricular disturbances [8] and impairment of the balance between vasoconstrictors and vasodilators, such as prostaglandins and nitric oxide (NO) [9,10]. However, there is still no clear explanation for all the aspects that may underlie these findings.…”
Section: Introductionmentioning
confidence: 99%
“…plasma uric acid, melatonin, reduced thiols), and oxidatively-generated substrates (e.g. plasma malondialdehyde, urinary 8-OHdG) exhibit strong circadian or other temporal fluctuations in amount or activity (Bridges et al 1992a;Hardeland et al 2003;Kanabrocki et al 2002Kanabrocki et al , 2004Kanabrocki et al , 2000Luo et al 1997;Niklowitz et al 2006;Reiter et al 1996;Valencia et al 2001). Whether the afternoon peak in salivary protein carbonyls (present study) is due to diurnal deficiencies in salivary gland / orophayngeal antioxidant defenses or augmented ROS production remains unclear.…”
Section: Discussionmentioning
confidence: 84%